2007
DOI: 10.1111/j.1464-410x.2007.06676.x
|View full text |Cite
|
Sign up to set email alerts
|

Using gene chips to identify organ‐specific, smooth muscle responses to experimental diabetes: potential applications to urological diseases

Abstract: OBJECTIVE To identify early diabetes‐related alterations in gene expression in bladder and erectile tissue that would provide novel diagnostic and therapeutic treatment targets to prevent, delay or ameliorate the ensuing bladder and erectile dysfunction. MATERIALS AND METHODS The RG‐U34A rat GeneChip® (Affymetrix Inc., Sunnyvale, CA, USA) oligonucleotide microarray (containing ≈8799 genes) was used to evaluate gene expression in corporal and male bladder tissue excised from rats 1 week after confirmation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 72 publications
2
28
0
Order By: Relevance
“…Other proteins, including myosin regulatory light chain 2-B smooth muscle isoform (Mrlcb) and Argbp2 showed STZ-induced increases at 1 week but no significant change at 2 months. Consistent with our 2D DIGE results for Mrlcb and calponin (Cnn1), in a recent genome expression analysis Hipp et al (20) found significant increases in Mrlcb and decreases in Cnn1 after 1 week of STZ-induced diabetes. 48 proteins showed STZ-induced differential expression 2 months after the confirmation of STZ-induced hyperglycemia.…”
Section: Resultssupporting
confidence: 77%
“…Other proteins, including myosin regulatory light chain 2-B smooth muscle isoform (Mrlcb) and Argbp2 showed STZ-induced increases at 1 week but no significant change at 2 months. Consistent with our 2D DIGE results for Mrlcb and calponin (Cnn1), in a recent genome expression analysis Hipp et al (20) found significant increases in Mrlcb and decreases in Cnn1 after 1 week of STZ-induced diabetes. 48 proteins showed STZ-induced differential expression 2 months after the confirmation of STZ-induced hyperglycemia.…”
Section: Resultssupporting
confidence: 77%
“…the different isoforms of collagens at both the transcriptional (32,33) and translational levels (Ref. 42 and this study) has yet to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…Animal Preparation-Diabetes was induced in male Fischer 344 rat (Taconic Farms, Germantown, NY; 8 -10 weeks old and weighing 200 -240 g) with a single intraperitoneal injection of STZ (35 mg/kg) dissolved in citrate buffer (0.6 M citric acid, 0.08 M Na 2 HPO 4 , pH 4.6) as described previously (33,42,49). The age-matched control (AMC) rats received an injection of vehicle only.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations